Pembebasan Dan Pemberdayaan: Teologi Sosial Hasan Hanafi Dalam Konteks Tafsir Perempuan Berkemajuan Buya Hamka - Andi Malaka; Mochamad Fadlani Salam (Andragogia: Journal Education Science And Islamic Studies, 2024)
The synergy between Hasan Hanafi's social theology and Buya Hamka's interpretation in the context of women's liberation and empowerment is explored in this paper. Hasan Hanafi, through his liberation theology, emphasizes the importance of real action to achieve social justice and equality. Meanwhile, Buya Hamka, with his humanistic and contextual approach to interpretation, emphasizes the values ??of justice, compassion and humanity in understanding the Qur'an. This research uses a qualitative approach, which is an understanding of the Koranic text as a research object. This research lies in an interdisciplinary approach that combines social theology with women's interpretation and Hasan Hanafi's social theology which can complement each other in efforts to liberate and empower women. This research aims to analyze how these two ideas can work together to create a holistic approach in overcoming social and gender injustice, as well as developing strategies for women's liberation and empowerment. The research results show that there are similar values ??and principles between Hasan Hanafi's social theology and Buya Hamka's interpretation, especially in terms of social justice and gender equality. This synergy produces a comprehensive approach, combining social action with contextual religious understanding. The implementation of this synergy can be applied in various fields such as education, health, public policy and economic empowerment. This article makes a new contribution by proposing a synergy model between social theology and Al-Qur'an interpretation as a strategy for women's empowerment that has not been widely discussed in previous literature. This approach not only provides practical solutions but also forms a framework that enables sustainable social change.